Aesthetic Criteria of an Artistic Image - Kadirova Dilbar Salixovna (International Journal on Integrated Education, 2023)
In this article, the aesthetic criteria of the artistic image, which is one of the most important factors of artistry in the general theoretical issues of art, are analyzed on the example of colors, and the history of the origin of views on colors, the influence of colors on human emotions in terms of symbolism and conditionality in colors are studied.